The impact of macro-economic growth on the income distribution in Ireland 1987-2004 - O'Donoghue, Cathal (Statistical and Social Inquiry Society of Ireland, 2006)
The Republic of Ireland has been the fastest growing economy in the OECD over the latter half of the 1990?s, an expansion known as the Celtic Tiger. Some commentators have commented on the gains from the boom being concentrated amongst the top of the income distribution. In this paper we shall try to understand what has happened to inequality over the period 1987-2004 and to understand the determinants of the changes in inequality.
Barrington Lecture 2005/2006
Read before the Society, 7th April 2006
Keywords: Wealth distribution; Economic growth; 314.15